2015
DOI: 10.1016/j.mee.2015.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Laser contact through electrosprayed alumina inverse opals on silicon

Abstract: In crystalline silicon (c-Si) solar cell field, an intensive effort is being paid to reduce the quantity of silicon material used in each cell in order to minimize its costs. With the reduction of wafer thickness, light trapping inside the cSi absorber becomes more and more necessary. Several photonic structures have been proposed underlining their optical properties. However, addressing other technological issues, like contact formation through the photonic structure, is also necessary for their application i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Inverse opal materials are gaining interest as photonic crystals [1], catalytic supports, capacitors [2], and photocatalytic devices [3], among others. Although it is possible to fabricate inverse opals by lithographic or ion beam techniques [4], self-assembly process is more flexible and cost effective for production [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inverse opal materials are gaining interest as photonic crystals [1], catalytic supports, capacitors [2], and photocatalytic devices [3], among others. Although it is possible to fabricate inverse opals by lithographic or ion beam techniques [4], self-assembly process is more flexible and cost effective for production [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Then the needle is polarized from -4 kV to -7 kV, and at the same time the sample is polarized with a high negative voltage, typically between -500 to -1000 V. This technique creates a fine aerosol of charged droplets that, as they reach the surface, induce an ordered deposit of the nanoparticles, due to electrokinetic and drag forces produced by the meniscus of the water while drying. Combining this technique with atomic layer deposition (ALD), it has been shown that inverse opals can be created by filling the inner voids of the ordered nanoparticles ending up in the inverse geometry of a colloidal crystal [2]. Although it has been shown that these structures exhibit good thermal stability [2], there is not any knowledge on the mechanical properties of these layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works [ 37 – 40 ] we have shown how an electrospray process of nanofluids can be used to deposit in a very short time very well ordered and with few defects layers (colloidal crystals) of polystyrene (of good quality and size) or silicon dioxide nanoparticles with dimensions typically several hundreds of micrometers with a close packed, face-centered cubic, three-dimensional order. In parallel we have shown the use of Al 2 O 3 as a good candidate for the inverse opal supporting layer regarding the low temperature deposition capacity and mechanical properties [ 41 42 ]. The main purpose of this article is to apply this technique to the fabrication of inverse opals using the 3D polystyrene nanoparticle template which enables the creation of large scale, large thickness, self-assembled structures with minimum fabrication errors and Al 2 O 3 /TiO 2 as a structural layer infiltrated through the voids.…”
Section: Introductionmentioning
confidence: 99%
“…Finally we observed that the pumping rate and the conductivity of the liquid had a minor impact. Details are given in references [9],[15] and [16]. In this paper, the importance of the dielectrophoretic force in the self assembly process is described.…”
Section: Introductionmentioning
confidence: 99%